The TDR Tuberculosis Specimen Bank : A Resource for Diagnostic Test Developers - Nathanson, C. M.; Cuevas, L. E.; Cunningham, J.; Perkins, M. D.; Peeling, R. W.; Guillerm, M.; Moussy, F.; Ramsay, A. (2012)
BACKGROUND: The Special Programme for Research and Training in Tropical Diseases established a specimen bank in 1999 to support the development and evaluation of new tuberculosis (TB) diagnostic tools. OBJECTIVE: To provide a narrative of the bank's development and discuss lessons learned, the bank's limitations and potential future applications. RESULTS: Collection sites were selected in high- and low-prevalence settings. Patients with TB symptoms, consenting to participate and to undergo human immunodeficiency virus testing were enrolled and diagnosed. Serum, sputum, saliva and urine samples were collected and sent to the bank's repositories. The bank has stocked 41,437 samples from 2524 patients at 11 sites worldwide. Ninety-five requests for specimens have been reviewed and 67 sets have been approved. Approved applicants have received sets of 20 or 200 samples. The bank allowed an evaluation of 19 commercial lateral flow tests and showed that none of them had broad global utility for TB diagnosis. CONCLUSIONS: The establishment and development of the specimen bank have provided a wealth of experience. It is fulfilling a need to provide quality specimens, but the type and number of samples may not fulfil the demands of future end-users. Plans are underway to review the mechanisms of specimen collection and distribution to maximise their impact on product development.